The reflection and re-emission coefficients of hydrogen particles impinging from plasma on the wall in the torsatron Uragan-3M - Bondarenko, V.N.; Petrushenya, A.A. (Вопросы атомной науки и техники, 2017)
The modelling of the radial emissivity profiles of Hα and Hβ lines radiated from hydrogen plasma of the torsatron Uragan-3M in a typical operational regime requires the usage of the programming code KN1D to consider a balance of atom and molecule fluxes on the walls. For this purpose, the reflection and re-emission coefficients were calculated of H atoms and H₂ molecules leaving the plasma and impinging on the plasma-facing surfaces of the stainless steel casings of a helical winding. Моделирование радиальных профилей интенсивности линий Hα и Hβ, излучённых из водородной плазмы торсатрона Ураган-3М в типичном рабочем режиме, требует использования программного кода KN1D для рассмотрения баланса атомных и молекулярных потоков на стенках. С этой целью были вычислены коэффициенты отражения и реэмисии атомов H и молекул H₂, покидающих плазму и падающих на обращённые к плазме поверхности кожухов винтовой обмотки из нержавеющей стали. Моделювання радіальних профілів інтенсивності ліній Hα і Hβ, випромінених з водневої плазми торсатрона Ураган-3М у типовому робочому режимі, вимагає використання програмного коду KN1D для розгляду балансу атомних і молекулярних потоків на стінках. З цією метою були обчислені коефіцієнти відбиття і реемісії атомів H і молекул H₂, які покидають плазму і падають на повернені до плазми поверхні кожухів гвинтової обмотки з нержавіючої сталі.